Educational Evaluation Regarding the Legislative Changes of Work Ofences and Especially of Work Abuse - Macovei, Cristian; Stanciu, Lidia (Acta Universitatis Danubius. Juridica, 2023)
As in other public fields and in that of education, work ofences can be committed, the most common being those of „abuse at work* and respectively *negligence at work*. There are well-known cases of violations of the legislation regarding the remuneration of teachers/violation of some of their rights or the behavior of teachers towards students (when a situation of inferiority is created for them based on race, nationality, ethnic origin, language, religion , sex, sexual orientation, etc.). These offenses are contained and provided for in the final and current form of Chapter II of Title V of the Criminal Code, entitled "Work offences".